Application of whey protein isolate fibrils in encapsulation and protection of β-carotene. (1st June 2021) - Zhang, Chao; Fu, Yuying; Li, Zeya; Li, Teng; Shi, Yugang; Xie, Hujun; Li, Yuan; Su, Huanhuan; Li, Zhenpeng
Highlights: The whey protein isolate fibrils (WPIF) were prepared through heating at pH 2.0. Fibrils improved the stability of β-carotene at pH 3.2. WPIF interacted with β-carotene was by hydrophobic interactions and hydrogen bond. β-carotene showed better bioavailability through the formation of WPIF/β-carotene complexes. Abstract: β-Carotene (BC) exhibits several bioactive properties, but its application is restrained due to the unstability and low biological availability. In this study, protein fibrils were prepared from whey protein isolate fibrils (WPIF), which were used as carriers to protect and deliver BC. With the extension of heating time, the molecular weight of WPI decreased gradually. WPI was hydrolyzed into peptides which self-assembled into WPIF, resulting in significant changes in secondary structure, zeta-potential, viscosity and, antioxidant capacity. The main interactions between WPIF and BC were hydrogen bonding and hydrophobic interaction. The encapsulation efficiency of WPIF24 was increased from 76.55% to 92.11% compared to that of untreated WPI. Moreover, the simulated gastrointestinal release showed that the cumulative release of BC encapsulated by WPIF24 reached the maximum in the simulated intestine. Therefore, WPIF could be a potential delivery system for water-insoluble bioactive compounds with enhanced encapsulation efficiency and protection effect.